William R. Long adjusting his senior project - Gus Beck::::::::: (1954)
Caption on back reads: 'William R. Long, senior electrical engineering major from Saugus, Massachusetts; makes final adjustment on his senior project -- application of the amplidyne generator in a servo-mechanism. This can be seen in the electrical engineering department display during Poly Royal.'